Pengaruh Kondisi Operasi pada Pembuatan Green Diesel dari MinyakNyamplung dengan Katalis NiMo/Al2O3 dan NiW/Al2O3 - Sumbogo Murti S.D.; Joni Prasetyo; Galuh Wirama M; Adiarso Adiarso (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
The attractiveness of biodiesel as an alternative fuel compared to fossil fuels because it has many advantages such as the availability of abundant raw materials, more environmentally friendly, high combustion efficiency, low sulfur content, high cetane number and biodegradability. Making biodiesel from callophylum inophyllum oil has been done through the hydrogenation process. Callophylum inophylum oil was treated via degumming and neutralisation to remove all impurities before hydroprocesing. Hydroprocessing was carried out in a 500ml autoclve at 30 – 50 MPa of initial hydrogen pressure, 300 – 400 oC of reaction temperature and equiped with stirrer and cooling sistem. NiMo/Al2O3 or NiW/Al2O3 was activated with CS2 mixture at 370 oC prior to the reaction. Some physical and chemical properties of the catalytic hydroprocessing product have been investigated in accordance to ASTM standard. The measurement result of product varies according to the operation condition. The result showed that calophyllum inophullum oil can be used as raw material for green diesel over NiMo/Al2O3 and NiW/Al2O3. Sulfided NiMo/Al2O3 catalysts are preferred due to high diesel yield.